[About CEU - Interviews]
Interview with Miklós Vásárhelyi, former member of the CEU Board of Trustees, former Chair of the Board of Trustees and one of the founders of the University. He talks about the history of the idea of the CEU. The second interview is with Professor János Kis who highlights the similarities and differences between the American schools and the CEU as a Western-type university. The third interview is with George Soros, businessman, philanthropist and the main founder of the CEU who touches upon the changes in the CEU since its beginnings.